Damage Detection in Structure using natural frequency - Sweta Verma; Pradeep Kumar; Novel Kumar Sahu (International Journal of Scientific Research in Civil Engineering, 2022)
Steel, Power and construction are the indispensable industries for progressive economic and social development. For maintenance purpose are inspected on regular basis. The main point is to examine and is useful for the detection of surface damages cracks, concrete spalling in the structure, corrosion of steel members, and incomplete failure components, they can be particularly limited at detecting embedded and minor damage, For example fatigue cracks in the structure, corrosion of reinforcement, and delamination. Today in the arena of the globalization, the concept of detection of damages based on dynamic measurement of structures is critical in focusing on the power of the modern city. It is based on changes in natural frequencies, flexibility and modal curvatures. However, the damage influence for each mode shape was studied based on combined modal. The frequency measurements before and after damage to locate the damage and estimate its severity in shear buildings. The changes induced by damage in the dynamic response are exploited to build a procedure for damage detection based on the variation of natural frequencies; both for continuous and discrete models of beams affected by concentrated damages are able to extract the relevant information from each mode shape. Some applications of the technique proposed are outlined their capacity to detect and localize damage will be analyzed in different cases. The method is further evaluated by vibration tests of two frame models. Shear in buildings, damage severity and locations can be accurately inferred using the present method. Structural health monitoring systems to replace conventional non-destructive inspection techniques, which require considerable downtime, human effort and cost. Vibration based damage detection, is the most promising techniques for implementation in Structural Health Monitoring (SHM).
Keywords: Damage Indicator; Modal Analysis; Cantilever Beam Damage Detection; Sensitivity Analysis; Frame Structure; And Modal Sensitivity